2015
DOI: 10.1038/ismej.2015.140
|View full text |Cite
|
Sign up to set email alerts
|

The composition of the zebrafish intestinal microbial community varies across development

Abstract: The assembly of resident microbial communities is an important event in animal development; however, the extent to which this process mirrors the developmental programs of host tissues is unknown. Here we surveyed the intestinal bacteria at key developmental time points in a sibling group of 135 individuals of a model vertebrate, the zebrafish (Danio rerio). Our survey revealed stage-specific signatures in the intestinal microbiota and extensive interindividual variation, even within the same developmental sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

69
573
8
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 542 publications
(659 citation statements)
references
References 38 publications
69
573
8
9
Order By: Relevance
“…We found that partitions clustered strongly based on whether and how they deviated from the neutral prediction (that is, above, below or within the neutral prediction) across host age (permutational MANOVA r 2 = 0.19, Po0.001; Figure 3a). Thus, the phylogenetic composition of the sub-groups that diverge from neutral patterns remains relatively similar across host development, despite the composition of communities as a whole changing (Stephens et al, 2015). Across age groups, non-neutral partitions of the metacommunity were also much more homogeneous than the neutral partitions, (ANOVA, Po0.01; illustrated by the spread of points in Figure 3a).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…We found that partitions clustered strongly based on whether and how they deviated from the neutral prediction (that is, above, below or within the neutral prediction) across host age (permutational MANOVA r 2 = 0.19, Po0.001; Figure 3a). Thus, the phylogenetic composition of the sub-groups that diverge from neutral patterns remains relatively similar across host development, despite the composition of communities as a whole changing (Stephens et al, 2015). Across age groups, non-neutral partitions of the metacommunity were also much more homogeneous than the neutral partitions, (ANOVA, Po0.01; illustrated by the spread of points in Figure 3a).…”
Section: Resultsmentioning
confidence: 90%
“…For the present study, we used a 16S rRNA gene sequence data set from a previously reported longitudinal study of the developing zebrafish intestinal microbiome (Stephens et al, 2015). A brief description of the study design and sample collection follows, and readers are referred to Stephens et al (2015) for additional details.…”
Section: Zebrafish Microbiota Longitudinal Studymentioning
confidence: 99%
See 3 more Smart Citations